Marital Resilience factors that enhance Conflict Management in Black African Marriages in South Africa: An Afro-Centric Perspective - Andrew Spaumer; Azwihangwisi Helen Mavhandu-Mudzusi; Segun Emmanuel Adewoye (E-Journal of Religious and Theological Studies)
Despite the stressful conditions and difficulties that bring about habitual conflict in many Black African marriages, some couples choose to manage their conflict and remain married, even in the context of the divorce culture. It is important to determine the potential factors that impact marital resilience in the midst of difficulties. Therefore, the purpose of this study was to explore resilience factors that enhance conflict management in Black African marriages in South Africa. A phenomenological research design was adopted using a qualitative research approach. Forty participants, consisting of 20 married men and 20 married women, were purposively selected to participate in this study. Data was collected using semi-structured individual and focus group interviews which were also audio-recorded. Following recordings, the interviews were transcribed. The data was analysed using inductive thematic analysis. The findings of this study demonstrated that, of all the techniques employed to handle marital crises, effective communication was the most widely favoured. Leaving things alone by opting to remain silent, being humble, and pastoral counselling were also found to be effective tactics. The findings of this study may be useful in therapeutic work with couples. The factors that participants identified as vital in contributing towards their marital resilience may be helpful to add to the understanding of marital resilience and may be used to develop a strengths-based intervention program for couples in marital crisis.